2006
DOI: 10.1055/s-2005-872951
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Limits of Bronchial Closure Methods in an Animal Model

Abstract: This trial suggests that manual suture closure using an appropriate technique and monofilament materials is as safe as the stapler.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…Some authors have reported that mechanical staplers are superior to manual suture for bronchial closure (13), while others found no difference (11). In an ex vivo study LUDWIG et al found a significantly higher air pressure resistance when the bronchus was closed with a mechanical stapler compared to manual suture (14).…”
Section: Discussionmentioning
confidence: 95%
“…Some authors have reported that mechanical staplers are superior to manual suture for bronchial closure (13), while others found no difference (11). In an ex vivo study LUDWIG et al found a significantly higher air pressure resistance when the bronchus was closed with a mechanical stapler compared to manual suture (14).…”
Section: Discussionmentioning
confidence: 95%
“…Combinations described in the literature include the use of manual intracorporeal suturing for bronchial closure along with vessel-sealing of the pulmonary vasculature [1,3] or the use of 5 mm endoscopic clips on the bronchus [2,3]. Although intracorporeal suturing techniques have been demonstrated to have similar leak pressures to endoscopic stapling devices, the increased surgical time may result in increased morbidity and cost associated with surgery [12,13]. A rapid and secure alternative to intracorporeal suturing techniques in small patients undergoing VATS lung lobectomy might decrease anesthesia and surgical time, which is especially appealing in this cohort of challenging patients that are often afflicted with significant pulmonary disease.…”
Section: Discussionmentioning
confidence: 98%
“…Šiuo metodu galima imituoti visus operacinėje atliekamus chirurginius veiksmus: paruošti tinkamo ilgio ir formos pagrindinio broncho bigę, labai tiksliai perverti siūlus. Eksperimentuojant nustatytas labai įvairus (nuo 33 iki 200 mmHg stulpelio) pagrindinio broncho bigės siūlės atsparumas slėgiui (7,(16)(17)(18)(19). Tai galima paaiškinti metodikos savitumais ir subjektyviais veiksniais, pvz., siūlės suveržimo laips-niu.…”
Section: Rezultatų Aptarimasunclassified